The Different Effects of IFN-β and IFN-γ on the Tumor-Suppressive Activity of Human Amniotic Fluid-Derived Mesenchymal Stem Cells - Jingchun Du; Anqi Liu; Rui Zhu; Chengbo Zhou; Heng Su; Guie Xie; Yingshan Deng; Xia Xu (Stem Cells International)
Current studies have shown that type I or II interferon-modified mesenchymal stem cells have great potential for the application of tumor-targeted therapy, but the underlying mechanism remains largely elusive. Here, we compared the different effects of IFN-β and IFN-γ on the antitumor activity of human amniotic fluid-derived mesenchymal stem cells (AFMSCs) and revealed the potential mechanism. In detail, AFMSCs primed with IFN-β or IFN-β plus IFN-γ, not IFN-γ, inhibited the proliferation of cancer cells in an immunocompetent mouse H460 subcutaneous model, although they all inhibited the proliferation of cancer cells in an immunocompromised mouse H460 subcutaneous model. TRAIL expressed by IFN-β- or IFN-γ-primed AFMSCs specifically exerted the antitumor effect of AFMSCs. AFMSCs primed with IFN-γ highly expressed immunosuppressive molecule IDO1, but IFN-β counteracted the IFN-γ-initiated IDO1 expression. 1-MT (IDO1 inhibitor) decreased TRAIL, but increased IDO1 expression in AFMSCs primed with interferon. As a result, AFMSCs primed with IFN-β or IFN-γ had the antitumor activity, and 1-MT failed to enhance the antitumor effect of IFN-γ-primed AFMSC in vitro and in the immunocompromised mouse H460 subcutaneous model. Furthermore, the expression of TRAIL in AFMSCs was upregulated by apoptotic cancer cells and this positive feedback intensified the antitumor effects of IFNs-primed AFMSCs. The different target gene expression profiles of AFMSCs regulated by IFN-β and IFN-γ determined the different antitumor effects of IFN-β- and IFN-γ-primed AFMSCs on tumor cells. Our finding may help to explore a clinical strategy for cancer intervention by understanding the antitumor mechanisms of MSCs and interferon.